1995
DOI: 10.1007/bf00202680
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced phase transitions in tridymite: an infrared spectroscopy study

Abstract: Abstract. The temperature dependence of the infrared active modes of meteoritic and synthetic tridymite have been investigated between 23 K and 1073 K in IR absorption and IR emission experiments. At room temperature both tridymite samples consist of a mixture of low temperature forms, in different proportions, due to the grinding. The sequence of phase transitions in Steinbach tridymite deduced from the IR data agrees well with recent X-ray and calorimetry studies using identical samples (Cellai et al. 1994).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…De Dombal and Carpenter (1993), in the DSC measurements of Steinbach tridymite, found two peaks at about 102 and 110 C and also found, in their infrared (IR) measurements, a significant change of the wave number of a mode at about 800 cm 1 at around 100 C. In the IR measurements of hand ground Steinbach tridymite by Cellai et al (1995), a band at 540 cm 1 showed two discontinuities in the temperature dependence of the intensity at 75 and 100 C, and then disappeared at 115 C: these authors consider that the first discontinuity (at 75 C) is related to the (MX 1) PO transition and the second one (at 100 C) to the MC OS transition, which occurs at about 115 C. These data in the IR and DSC experiments lead Cellai et al (1995) to conclude that the transition MC OS or MC OP apparently proceeds via an intermediate phase, which exists in a small temperature interval of about 12 C. The existence of the intermediate phase is also stressed by Pryde and Dove (1998) in a symmetry point of view for the related phases.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…De Dombal and Carpenter (1993), in the DSC measurements of Steinbach tridymite, found two peaks at about 102 and 110 C and also found, in their infrared (IR) measurements, a significant change of the wave number of a mode at about 800 cm 1 at around 100 C. In the IR measurements of hand ground Steinbach tridymite by Cellai et al (1995), a band at 540 cm 1 showed two discontinuities in the temperature dependence of the intensity at 75 and 100 C, and then disappeared at 115 C: these authors consider that the first discontinuity (at 75 C) is related to the (MX 1) PO transition and the second one (at 100 C) to the MC OS transition, which occurs at about 115 C. These data in the IR and DSC experiments lead Cellai et al (1995) to conclude that the transition MC OS or MC OP apparently proceeds via an intermediate phase, which exists in a small temperature interval of about 12 C. The existence of the intermediate phase is also stressed by Pryde and Dove (1998) in a symmetry point of view for the related phases.…”
Section: Introductionmentioning
confidence: 87%
“…For the first, X ray single crystal intensities were newly measured with a nearly twin free crystal on a diffractometer equipped with a charge coupled device (CCD) detector. For the second, DTA measurements were carried out on powdered samples prepared to be of the single phase of MC tridymite, and the unit cell parameters were measured with a single crystal at various temperatures including the MC OP transition point, focusing on the reported intermediate phase (Cellai et al, 1995). For the third, Raman spectroscopic data were measured for MC, OP and the higher temperature phases of tridymite: these data are not only the first to be reported but are informative in respect of the second objective.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectrum from unirradiated tridymite (T03) exhibits several peaks at around 209, 293, 362, 405, and 425 cm −1 , which can be assigned to atomic vibrations related to Si and O bending in the tetrahedra, based on previous reports by Etchepare et al (1978), Kingma and Hemley (1994), and Cellai et al (1995) (Fig. 11a).…”
Section: Micro-raman Measurementsmentioning
confidence: 95%
“…This may be interpreted in the same way as the quenching mechanism. The lattice vibration energies of tridymite and cristobalite can be obtained from Raman and IR spectroscopy data (e.g., Bates 1972;Etchepare et al 1978;Kingma and Hemley 1994;Cellai et al 1995). In tridymite, O-Si-O bending vibration energy is 0.025-0.027 eV (202-218 cm −1 ) and Si-O stretching vibration energy is 0.13-0.14 eV (1049-1130 cm −1 ); in cristobalite, the former is 0.028-0.034 eV (226-274 cm −1 ) and the latter is 0.15-0.16 eV (1211-1249 cm −1 ).…”
Section: Temperature Quenching Effectsmentioning
confidence: 99%
“…At higher temperatures ( Fig. 3(b)) there are numerous much smaller anomalies, corresponding to Downloaded by [Temple University Libraries] at 05:20 19 November 2014 transitions between different orthorhombic and hexagonal structures (reviewed most recently by Smelik andReeber, 1990, andCellai et al, 1995). Autocorrelation analysis of IR absorption spectra from Steinbach tridymite reveals a systematic variation of the effective line width of a group of overlapping peaks in the frequency range 247-681cm-' in terms of a parameter A C O I T~~.…”
Section: Microscopic Strains Spectral Line Broadening and Enthalpymentioning
confidence: 97%